Rancang Bangun Sistem Informasi Pengelolaan Ternak Udang Vaname Berbasis Web di Aceh Besar - Siti Meli; Mukhroji Mukhroji; Rossiana Br Ginting (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
Data management in vaname shrimp (Litopenaeus vannamei) farming businesses is a critical factor in supporting smooth pond operations, yet most farmers in Aceh Besar still rely on manual, paper-based recording. This practice frequently causes recording errors, difficulty retrieving data, and delays in preparing production reports. This study aims to design and develop a Web-Based Vaname Shrimp Farm Management Information System at Tambak Udang Vaname Intensif Kurnia, Aceh Besar, to help pond owners manage production and sales data more effectively and efficiently. The system was developed using a qualitative, software-engineering approach following the Waterfall model, with data collected through observation, interviews, and a literature review. The system was built using the PHP programming language with the CodeIgniter framework and MySQL as the database management system. The resulting system provides shrimp-type data management, stock management, online product ordering, payment management, and automatic report generation. Black-box testing and usability evaluation with the pond owner indicate that the system successfully computerises pond data management, eases data storage, retrieval, and processing, reduces recording errors, and provides faster, more accurate information for decision-making. The Web-Based Vaname Shrimp Farm Management Information System can therefore serve as an effective solution for supporting vaname shrimp farming businesses in Aceh Besar and similar coastal regions